Soil quality effects on Chenopodium album flavonoid content and antioxidant potential - Chludil, Hugo Daniel (2008)
Antioxidant capacity, total phenolic content and flavonoid glycosides profile were compared in C. album samples grown in intensively cultivated (IC) and nondisturbed (ND) soils to evaluate differences in their nutraceutical potential. Petroleum ether, methanol, and aqueous extracts were sequentially obtained from C. album dried samples. Methanol crude extract exhibited the highest antioxidant potential and phenolic content, which were significantly enhanced by soil deterioration. This feature was enhanced in its ethyl acetate/n-buthanol subextract that also yielded higher amounts of the fraction containing flavonoid glycosides in samples grown in IC soils. Compounds were isolated by activity-guided fractionation, and chemical structure−antioxidant activity relationships were established. Chemical structures were elucidated by chemical and spectroscopic methods. Six known flavonoid glycosides were isolated, and their antioxidant activity was determined by DPPH assay. 1, quercetin-3-O-(2′′,6′′-di-O-α-l-rhamnopyranosyl)-β-d-glucopyranoside; 2, kaempferol-3-O-(2′′,6′′-di-O-α-l-rhamnopyranosyl)-β-d-glucopyranoside; 3, quercetin-3-O-β-d-glucopyranosyl-(1′′′→6′′)-β-d-glucopyranoside; 4, rutin; 5, quercetin-3-O-β-d-glucopyranoside; and 6, kaempferol-3-O-β-d-glucopyranoside. Triosides 1 and 2 were identified for the first time in C. album. Our results suggest that this edible weed, ubiquitously present in cultivated fields, should be considered as a nutraceutical food and an alternative source for nutrients and free radical scavenging compounds, particularly when collected from cultivated fields that seem to increase some of its advantages.